Environmental disclosure, financial performance, and firm value in the mining and manufacturing industry - Sayuti, Alfian; Mohammed, Nor Farizal; Amirrudin, Mira Susanti (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
Mining is an integral pillar of Indonesia’s emerging market economy, contributing 9% of the total GDP in 2022, while the manufacturing sector grew by 5.01% in 2022. This study investigated the effect of environmental disclosure (ED) on firm value (FV) in Indonesia’s mining and manufacturing sectors, with financial performance as a moderating factor. Using a sample of 260 data points from companies listed in the Indonesia Stock Exchange between 2020 and 2021, we employed multiple regression models to analyze the data. Our findings revealed that environmental disclosure did not have a significant direct impact on firm value. However, financial performance strengthened the positive relationship between environmental disclosure and firm value, suggesting that investors placed more importance on financial performance than on environmental disclosure alone. The results reflected the evolving but still cautious approach of Indonesian investors toward sustainability, offering insights into investor behavior in developing markets. The study contributes to literature by providing a new perspective on signaling theory in the context of emerging economies and highlights the need for future research on the integration of environmental considerations into financial decision-making.